Factors influencing the return of post-consumer fluorescent lamps through reverse logistics in São Bento do Sul/SC (Brazil) - Vepech, Joari; Fagundes, Alexandre Borges; Beuren, Fernanda Hänsch; Vaz, Caroline Rodrigues (Revista DELOS, 2025)
THIS IS AN ARTICLE PUBLISHED BY Revista DELOS (e-ISSN: 1988-5245) ON 2025-05-06, AVAILABLE ONLINE: https://doi.org/10.55905/rdelosv18.n67-013 Abstract This article discusses the sectoral agreement on sodium and mercury vapor fluorescent lamps and mixed light within the framework of Reverse Logistics Systems, an instrument of the National Solid Waste Policy. The primary goal of this study was to identify the main factors influencing the quantities of unusable products returned to the system through Reverse Logistics in São Bento do Sul/SC. To achieve this, data were collected from domestic consumers, store owners, and the manager of the city's waste collection system. The respondents' opinions were then analyzed to identify potential factors and trends related to the research subject. Consequently, this research not only helped identify influencing variables but also offered insights into possible trends in consumer consumption and disposal behavior, providing a conceptual foundation and suggestions for future research in the field of reverse logistics.
Keywords: Fluorescent lamps; Reverse logistics; National Solid Waste Policy; Sectoral agreement